ANALYSIS OF NATIONAL AND FOREIGN EXPERIMENTS ON WORKING WITH GIFTED STUDENTS IN TEACHING MOTHER TONGUE - D. Pardaboyev (Web of Journals Publishing, 2024)
This article covers the use of national and foreign experience in bringing students ' talents to the surface when teaching native language subjects in the higher education system.
Keywords: student, talent, native language, speech, experience, foreign experience, National Experience, Innovation, innovative project, specialist.